OPTIMIZATION CONDITION OF HYDROGENATION OF PALM KERNEL OIL IN TRANS FAT FREE COCOA BUTTER SUBSTITUTE PRODUCTION - Hasrul Abdi Hasibuan (Widyariset, 2011)
Production of trans fat free cocoa butter substitute by hydrogenation of palm kernel oil has been concluded. This research was undertaken by reaction of palm kernel oil and hydrogen using variation of pressure, catalyst and reaction time were 100 to 200 Psi, 0.05 to 0.25% and 1 to 5 hrs, respectively. The characteristic of CBS was determined i.e. content of trans fatty acid, stearic acid, melting point, iodine value and solid fat content. The result of analysis showed that increasing of pressure, catalyst and reaction time were simultaneously increase stearic acid composition, melting point, solid fat content and it was decrease iodine value and trans fatty acid content. The optimum condition was achieved at pressure 150 Psi, catalyst 0.1% and reaction time 3 hr.